CARDIOVASCULAR DISEASES AND VITAL EXHAUSTION: LONGITUDINAL STUDY IN RUSSIA/SIBERIA (WHO MONICA — PSYCHOSOCIAL PROGRAM) - V. Gafarov; M. Voevoda; E. Gromova; V. Maksimov; I. Gagulin; N. Yudin; A. Gafarova; T. Mishakova (Российский кардиологический журнал)
Aim. To study prevalence rates of vital exhaustion and its effects on 14-year risk of cardiovascular disease (CVD) (arterial hypertension (AH), myocardial infarction (MI), and stroke) development and genetic traits in open population of 25–64-yearold men in Russia/Siberia (West Siberia metropolis, Novosibirsk).Material and methods. Random representative sample of 25–64-year-old men was studied in a framework of WHO MONICA-Psychosocial Program (MOPSY) in 1994. Maastricht Questionnaire (MQ) was used to assess vital exhaustion. Genotyping for variable number of tandem repeats (VNTR) polymorphisms in DRD4 and DAT genes was performed. All new cases of AH, MI, and stroke were registered among people without CVD for 14 years (from 1994 to 2008). Statistical analysis was done by using software package SPSS 11.5. Cox proportional hazards regression model was used for evaluation of risk coefficient (hazard ratio (HR) taking into account time-adjusted control. Х2 test was used to assess statistical significance of differences between the groups.Results. In the study population, the vital exhaustion rate was 66,8%. Hazard ration was significantly increased (AH: HR=3,2; MI: HR=2,7; stroke: HR=3,2) in men with vital exhaustion compared with vital exhaustion-free individuals in open population during the first five years of observation. Multifactorial modeling showed that vital exhaustion together with concomitant social gradient determined development of AH, MI, and stroke in open population of 25–64-year-old men. Allele 7 of DRD4 and genotype 9/9 of DAT gene were associated with high level of vital exhaustion.Conclusion: Open population of 25–64-year-old men (Russia/Siberia, Novosibirsk) showed high level of vital exhaustion, a predictor for risk of developing CVD. Vital exhaustion is significantly associated with certain VNTR polymorphisms of DRD4 and DAT gens.